Analisis Strategi Bauran Pemasaran Untuk Meningkatkan Jumlah Proyek Konstruksi Di Pt Prana Visi Media Jakarta. - Yusuf, Yassar Ramzy; Maulina, Anita; Arizona, Anisa (JAMBIS : Jurnal Administrasi Bisnis, 2023)
PT Prana Visi Media Jakarta is one of the construction companies that is facing an imbalances and disrupted project realization for the period 2020 to 2022. The purpose of this study was to analyze of The Marketing Mix Strategy to Increase the Construction Projects at PT Prana Visi Media Jakarta along with its obstacles and solutions reviewed through the 7P marketing mix and SWOT Analysis. This research was conducted using a descriptive qualitative approach with observation and interview techniques. The results showed that PT Prana Visi Media Jakarta project which includes housing, warehouses, offices, renovation/expansion and other projects during 2020 to 2022 has experienced up and down. Where in 2020 to 2021 housing and warehouse projects have the same, while office projects and renovation/expansion and other projects decrease in 2021 compared to 2020. However, 7P marketing mix strategy which is dominated by the product elements and SWOT Analysis that was carried out, PT Prana Visi Media Jakarta Projects has suceedded in increasing progress marked by an increase of construction projects in 2022 until now.